Trust-based Routing Protocols in Wireless Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
the Wireless sensor Networks is usually consisting of all-inclusive amount of bound sensor accessories which are announced in balance of the wireless media. As WSN’s become added and added capital to accustomed life, their aegis and assurance become a primary concern. However because of the attributes of WSNs, aegis architecture can be challenging. Trust-aware acquisition protocols play a capital role in aegis of Wireless Sensor Networks (WSNs). The key allotment of the acquisition agreement is avenue alternative based on account theory. Our after-effects announce that trust-based geographic acquisition approaches the ideal achievement akin accessible by flooding-based acquisition in bulletin supply arrangement and bulletin adjournment after incurring abundant bulletin overhead.